Drug Induced Sleep Endoscopy for Obstructive Sleep Apnea Syndrome: An Initial Experience in a Tertiary Level Centre - Parajuli, Bashu D; Mandal, Lokendra; Koirala, Megha; Bhattarai, Amit S; Neupane, Yogesh; Shrestha, Anil (Journal of Institute of Medicine Nepal, 2019)
Drug induced sleep endoscopy (DISE) is a technique of performing endoscopy of the upper airway after inducing sleep by the use of anaesthetic agents in patients suffering from obstructive sleep apnea syndrome (OSAS). The main purpose of DISE is to detect the obstruction or collapse at one or more location in the upper airway, both for the successful diagnosis and management of OSAS. Here we discuss a case of OSAS who underwent DISE under novel anaesthetic agents midazolam and dexmedetomidine.